Diseño de una ruta turística, para potenciar el turismo en Loma de La Virgen cantón La Maná, año 2022 - Robalino Jurado, Dennise Azucena (2022)
This project deals with the design of a tourist route, to promote tourism in the loma de la virgen belonging to the La Maná canton, with the same it is intended to encourage the inhabitants to carry out their different ventures and obtain economic benefits from this route, In addition, the public and private sectors are involved so that they can participate in joint work. The general objective is to promote tourism that has already been forming for several years and now with the facilities that exist due to digital media, they can be demonstrated locally, nationally and even internationally as a high-class tourist attraction. The lack of government initiatives in support of small businesses are what have briefly slowed down the positive growth in this area, due to bureaucratic procedures and the amount of taxes that a citizen must pay before starting a business, bringing as a consequence the migration of young people to large cities and in turn causes them to no longer be part of the campus and it is more difficult to form an organization that promotes and manages social media in search of increased tourism in this sector, however the desire to getting ahead and obtaining an income makes the residents still hope for better days, as well as the support of the competent entities.